An investigation of the effect of a short ICT training intervention on teachers' ability to integrate ICT into their teaching practice. - Khwela, Robert Mfaniseni (My University, 2015)
In this study I wished to understand whether my short-term training intervention enabled teachers to design and implement a lesson in which technology is effectively integrated. Participants were 22 teachers, some of whom held positions on their school’s management team, and 80 learners from 4 districts of the KwaZulu-Natal Department of Education. Teachers in the province have been trained in computer literacy; however, sadly, this did not automatically translate into classroom ICT integration. Overall, teachers do not integrate technology into their teaching. A number of reasons for this are identified. People involved in integrating technologies into the teaching and learning process have to be convinced of the value of the technologies, be comfortable with them, and be skilled in using them. Therefore, a short-term training intervention was designed to test whether it can benefit teachers by enhancing teaching and learning through communication and collaboration, by means of ICT. The results revealed that the teachers on the training programme gained knowledge of how to integrate ICT, that they collaborated, that their pedagogy also changed, and that their learners felt that their learning was improved. To ensure realistic and holistic solutions for policymakers, district and school officials, the factors that prevent teachers from making full use of ICT were also iterated. Detailed results and implications of the results are discussed.
Keywords: Short term intervention; Educator training; ICT integration; ICT training model